The way forward for nutrition-driven agriculture - Fan, Shenggen; Yosef, Sivan; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2019)
This volume has highlighted the important links between agriculture and nutrition, both direct and indirect, both theoretical and practical. It has explored these relationships through various frameworks, such as value chains, programs and policies, as well as through diverse perspectives, such as gender. It has assessed the impacts of various agricultural interventions and policies on nutrition, including those that integrate behavior change communication or social protection, and profiled the up-and-down journeys of countries such as Bangladesh, China, Ethiopia, India, and Malawi in integrating nutrition into agriculture policies and program interventions. It has highlighted successes such as biofortification, the integration of behavior change communication and gender equality into existing agricultural interventions, and agriculture’s role in improving household access to nutritious foods and diet diversity. It has analyzed challenges such as climate and environmental change, undernutrition, and obesity. And it has pondered big questions, such as how to build capacity, engage with the private sector, participate in the big data revolution, and foster strong governance and leadership throughout agriculture and nutrition.